2008
DOI: 10.1038/sj.bjc.6604246
|View full text |Cite
|
Sign up to set email alerts
|

Cortactin expression predicts poor survival in laryngeal carcinoma

Abstract: Amplification of the 11q13 region is one of the most frequent aberrations in squamous cell carcinomas of the head and neck region (HNSCC). Amplification of 11q13 has been shown to correlate with the presence of lymph node metastases and decreased survival. The 11q13.3 amplicon carries numerous genes including cyclin D1 and cortactin. Recently, we reported that FADD becomes overexpressed upon amplification and that FADD protein expression predicts for lymph node positivity and disease-specific mortality. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 40 publications
4
71
0
Order By: Relevance
“…CTTN encodes the actin-binding protein cortactin that regulates membrane dynamics, actin network assembly, cell-cell adhesion, invadopodia formation, and matrix degradation, thereby promoting cell motility and invasion (10)(11)(12). We and others have consistently shown that CTTN gene amplification and protein overexpression correlated with poor prognosis and reduced patient survival in HNSCC (13)(14)(15) and other carcinomas (16)(17)(18), thus reinforcing the central role of CTTN in the 11q13 amplicon and also in tumor progression. Nevertheless, the role of CTTN/cortactin in the early stages of tumorigenesis and its possible implication in malignant transformation and acquisition of an invasive phenotype remains to be determined.…”
Section: Introductionmentioning
confidence: 56%
“…CTTN encodes the actin-binding protein cortactin that regulates membrane dynamics, actin network assembly, cell-cell adhesion, invadopodia formation, and matrix degradation, thereby promoting cell motility and invasion (10)(11)(12). We and others have consistently shown that CTTN gene amplification and protein overexpression correlated with poor prognosis and reduced patient survival in HNSCC (13)(14)(15) and other carcinomas (16)(17)(18), thus reinforcing the central role of CTTN in the 11q13 amplicon and also in tumor progression. Nevertheless, the role of CTTN/cortactin in the early stages of tumorigenesis and its possible implication in malignant transformation and acquisition of an invasive phenotype remains to be determined.…”
Section: Introductionmentioning
confidence: 56%
“…Previous clinical studies of another invadopodia component, cortactin, indicate that its elevated expression and dysregulated cellular localization correlate with poor survival in laryngeal carcinoma and lung adenocarcinoma, respectively, underlining the relevance of invadopodia activity in predicting clinical outcomes (Gibcus et al 2008;Hirooka et al 2011). Consistent with these studies, our data show that a high level of Tks5 long expression and a low level of Tks5 short expression correlate with metastatic progression of lung adenocarcinoma patients and predict poor survival of patients with early stage disease, suggesting that the Tks5 long to Tks5 short ratio may serve as a prognostic marker for assessing the metastatic potential of primary tumors and for identifying early stage patients who bear higher risks for metastasis and may benefit from adjuvant therapy after tumor resection.…”
Section: Discussionmentioning
confidence: 99%
“…Cortactin (CTTN gene) has also been suggested as a potential metastatic driver from the 11q13.3 band, mediating an epithelial-to-mesenchymal switch through interactions with cytoskeletal components (Patel et al, 1998;van Rossum et al, 2006;Rothschild et al, 2006;Luo et al, 2006;Gibcus et al, 2008;Yamada et al, 2010). Regardless of mechanism, our results suggest that ANO1 copy number gain could act as a strong predictive marker for HPSCC tumours with a high risk of nodal metastasis.…”
Section: Genes Chromosomes and Cancermentioning
confidence: 99%